2010
DOI: 10.1097/ftd.0b013e3181cdc93e
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Repercussions of Analytical Interferences Due to Aldosterone Antagonists in Digoxin Immunoassays: An Assessment

Abstract: Analytical interferences in digoxin immunoassays constitute a well-known problem, with repercussions for therapeutic drug monitoring. Clinically effective doses of spironolactone and potassium canrenoate cross-react in several digoxin immunoassays, producing falsely elevated or lowered concentrations. This study evaluates the interferences caused by these drugs in the microparticle enzyme immunoassay (MEIA III) in comparison with another 3 immunoassays used for digoxin therapeutic drug monitoring: MEIA II, flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[3][4][5][6][7] This can lead to inappropriate digoxin dosing, which can potentially lead to serious problems for patients' health. [3][4][5][6][7] This can lead to inappropriate digoxin dosing, which can potentially lead to serious problems for patients' health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] This can lead to inappropriate digoxin dosing, which can potentially lead to serious problems for patients' health. [3][4][5][6][7] This can lead to inappropriate digoxin dosing, which can potentially lead to serious problems for patients' health.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, a New Zealand study has shown that clinicians were more inclined to dose patients based on their clinical situation when serum digoxin concentrations were low, whereas high digoxin concentrations were deemed to represent toxicity regardless of the patient's clinical impression. [4][5][6][7] However, a New Zealand study has shown that clinicians were more inclined to dose patients based on their clinical situation when serum digoxin concentrations were low, whereas high digoxin concentrations were deemed to represent toxicity regardless of the patient's clinical impression.…”
Section: Introductionmentioning
confidence: 99%